Developing a framework for successful research partnerships in global health. Issue 1 (December 2016) - Larkan, Fiona; Uduma, Ogenna; Lawal, Saheed; van Bavel, Bianca
Abstract Background The Centre for Global Health, Trinity College Dublin has as one of its goals, strengthening health systems in developing countries. In realising this goal we work across more than 40 countries with third-level, civil society, government, private sector and UN partners. Each of these requires that different relationships be established. Good principles must guide all global health research partnerships. An exploratory research project was undertaken with research partners of, and staff within, the Centre for Global Health. The aim was to build an evidence-based framework. Methods An inductive exploratory research process was undertaken using a grounded theory approach in three consecutive phases: Phase I: An open-ended questionnaire was sent via email to all identified partners. Phase II: A series of consultative meetings were held with the staff of the Centre for Global Health. Phase III: Data sets from Phases I and II were applied to the development of a unifying framework. Data was analysed using grounded theory three stage thematic analysis - open, axial and selective coding. Results Relational and operational aspects of partnership were highlighted as being relevant across every partnership. Seven equally important core concepts emerged (focus, values, equity, benefit, leadership, communication and resolution), and are described and discussed here. Of these, two (leadership and resolution) are less often considered in existing literature on partnerships. Conclusions Large complex partnerships can work well if all parties are agreed in advance to a common minimum programme, have been involved from the design stage, and have adequate resources specifically allocated. Based on this research, a framework for partnerships has been developed and is shared.